Three-dimensional Orbital Architectures and Detectability of Adjacent Companions to Hot Jupiters - Thomas MacLean; Juliette Becker (The Astrophysical Journal)
The orbital properties of the (as yet) small population of hot Jupiters with nearby planetary companions provide valuable constraints on the past migration processes of these systems. In this work, we explore the likelihood that dynamical perturbations could cause nearby inner or outer companions to a hot Jupiter to leave the transiting plane, potentially leaving these companions undetected despite their presence at formation. Using a combination of analytical and numerical models, we examine the effects of stellar evolution on hot Jupiter systems with nearby companions and identify several possible outcomes. We find that while inner companions are generally unlikely to leave the transiting plane, outer companions are more prone to decoupling from the hot Jupiter and becoming nontransiting, depending on the system’s initial orbital architecture. Additionally, we observe a range of dynamical behaviors, including overall stability, inclination excitation, and, in some cases, instability leading to the ejection or collision of planets. We also show that the effect of stellar obliquity (with respect to the mean planet of the planets) is to amplify these effects and potentially cause outer companions to attain nonmutually transiting configurations more often. Our results highlight the complex dynamical pathways shaping the architectures of hot Jupiter systems.